Delays in presentation and diagnosis of pulmonary tuberculosis: a retrospective study of a tertiary health service in Western Melbourne, 2011–2014. Issue 2 (7th February 2018) - Williams, Eloise; Cheng, Allen C.; Lane, Garry P.; Guy, Stephen D.
Abstract: Background: Effective tuberculosis (TB) control relies on early diagnosis and prompt treatment commencement. Aim: To investigate delays in presentation and diagnosis of pulmonary TB (PTB) in a low incidence setting in Western Melbourne. Methods: A single‐centred retrospective observational cohort study of symptomatic patients ≥ 18 years newly diagnosed with PTB that were commenced on treatment between 1 December 2011 and 1 December 2014 at a tertiary teaching hospital in Western Melbourne. Main outcome measures included median duration of patient, health system and total delays to diagnosis of PTB and clinical factors associated with prolonged patient (>35 days) and health system (>21 days) delay. Results: A total of 133 patients were included. The median (range) duration of patient, health system and total delay to diagnosis were 28 (0–610), 18 (0–357) and 89 (1–730) days respectively. Prolonged patient delay was associated with being from a country with an annual TB incidence of <50/100 000 (odds ratio (OR) 5.98, 95% confidence interval (CI) 1.19, 29.98) and diabetes mellitus (OR 3.02, 95% CI 1.04, 8.78) in multivariate analysis. Being Australian‐born or a resident of Australia ≥6 years (OR 0.03, 95% CI 0.12, 0.74; OR 0.30, 95% CI 0.00, 0.033 respectively) was associated with reduced patient delay. Conclusions: In this low‐incidence, high‐resource setting, patient delays contribute most to total delay in PTB diagnosis. Strategies addressing this aspect of the TB diagnosis pathway, such as health literacy and promotion programmes for new migrants and raised primary healthcare awareness, could have the largest impact on reducing total PTB diagnosis delays.